2002
DOI: 10.1021/tx020026z
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Dimethylarsinous Acid in Dimethylarsinic Acid-Induced Urothelial Toxicity and Regeneration in the Rat

Abstract: Dimethylarsinic acid (DMA(V)) is carcinogenic to the rat urinary bladder when administered at high doses in the diet or drinking water. At a dietary dose of 100 ppm (microg/g), it produces cytotoxicity within 6 h and increased proliferation (hyperplasia) by 7 days of administration. We hypothesize that formation of the reactive organic intermediate dimethylarsinous acid (DMA(III)) is involved in the induction of the cytotoxicity. To evaluate the possibility that DMA(V) administration produces urothelial toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 24 publications
3
104
2
Order By: Relevance
“…However, the activity of DMA(III) was still 1000-fold less than that of MMC (Table 2). DMA(V) gives similar effects on V79 cells as DMA(III) at more than 100-fold high concentrations of DMA(III) such as mitotic arrest, induction of tetraploids 25,32 and chromosomal aberration. 33 Cysteine enhances the cytogenetic toxic effects of DMA(V) in V79 cells to induce mitotic arrest, tetraploid formation and induction of chromosomal aberration, 33 and it also enhances cytotoxicity and induction of apoptosis in HL-60 cells.…”
Section: Discussionmentioning
confidence: 90%
“…However, the activity of DMA(III) was still 1000-fold less than that of MMC (Table 2). DMA(V) gives similar effects on V79 cells as DMA(III) at more than 100-fold high concentrations of DMA(III) such as mitotic arrest, induction of tetraploids 25,32 and chromosomal aberration. 33 Cysteine enhances the cytogenetic toxic effects of DMA(V) in V79 cells to induce mitotic arrest, tetraploid formation and induction of chromosomal aberration, 33 and it also enhances cytotoxicity and induction of apoptosis in HL-60 cells.…”
Section: Discussionmentioning
confidence: 90%
“…For example, the LD 50 s for As(III) in rats range from 15 to 145 mg As/kg, whereas the rat LD 50 for MMA is 2833 mg As/kg (male and female combined), and the rat LD 50 for DMA is 1935 mg/kgÁday (Agency for Toxic Substances and Disease, 2007;EPA, 2006). The lower toxicity of the methylated arsenic compounds via the oral route is observed with intermediate and chronic exposures as well (Agency for Toxic Substances and Disease Registry, 2007), and it has been shown repeatedly in in vitro studies (Cohen et al, 2002;Petrick et al, 2000). The pentavalent methylated metabolites of arsenic are generated from the metabolism of inorganic arsenic in animals (including humans), but they also occur naturally in the environment and serve as the active ingredient in the pesticides monosodium methanearsonate (MSMA), disodium methanearsonate (DSMA), calcium acid methanearsonate (CAMA), and cacodylic acid (U.S. Environmental Protection Agency, 2006).…”
Section: Arsenic Toxicologymentioning
confidence: 95%
“…Many in vitro studies have tested the toxicity of As(III) and As(V) in a common test system and have observed that As(III) is significantly more toxic than As(V). As an example, Cohen et al (2002) observed that the LC 50 for As(III) (sodium arsenite) in human bladder cells was 4.8 µM, whereas the LC 50 for As(V) (sodium arsenate) was 31.3 µM. Similarly, using the lactate dehydrogenase (LDH) assay, As(III) (LC 50 ¼ 68 AE 16.9 µM) was considerably more cytotoxic than arsenate (LC 50 ¼ 1,628 AE 110 µM) in a cell culture of human hepatocytes (Petrick et al, 2000).…”
Section: Arsenic Toxicologymentioning
confidence: 99%
“…In contrast, MMA V is negative as a carcinogen in rat and mouse bioassays but is a transplacental carcinogen in the mouse (Tokar et al, 2012). Thus, because the metabolism of iAs forms methylated metabolites that are more reactive and toxic than the parent compound (Cohen et al, 2002;Petrick et al, 2000;Styblo et al, 2000), it is likely that the methylated arsenicals contribute to the spectrum of adverse health effects associated with chronic exposure to iAs .…”
Section: Introductionmentioning
confidence: 99%